2018
DOI: 10.1002/aenm.201802108
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic High‐Rate Solar Steaming and Mercury Removal with MoS2/C @ Polyurethane Composite Sponges

Abstract: Solar steam generation, a sustainable water‐purification technology, holds substantial promise in resolving the global issue of shortage of drinkable water. Here, the design, fabrication, and high‐performance of an innovative 3D solar steamer, offering synergistic high‐efficiency steaming and heavy metal removal functions are reported. The device is made of synthesized carbon‐molybdenum‐disulfide microbeads electrostatically assembled on a 3D polyurethane sponge. The mesoporous composite sponge also serves as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 66 publications
1
84
0
Order By: Relevance
“…Thus, the overall concentrations of heavy metal ions were reduced by six to nine orders of magnitude (ppb) after simultaneous one‐step adsorption and solar distillation (Figure 5f), which is comparable with current purification techniques . In addition, Hg 2+ is well‐recognized for its evaporative property that is different to remove by simple distillation process . From Figure 5d,f, the concentration of Hg 2+ was lowered by seven orders of magnitudes due to the adsorption function.…”
supporting
confidence: 62%
“…Thus, the overall concentrations of heavy metal ions were reduced by six to nine orders of magnitude (ppb) after simultaneous one‐step adsorption and solar distillation (Figure 5f), which is comparable with current purification techniques . In addition, Hg 2+ is well‐recognized for its evaporative property that is different to remove by simple distillation process . From Figure 5d,f, the concentration of Hg 2+ was lowered by seven orders of magnitudes due to the adsorption function.…”
supporting
confidence: 62%
“…Besides developing low‐cost photothermal materials, it is of paramount importance to design solar steaming‐collection systems that can be efficient as well as portable to address the needs of people on individual levels. 3D superstructures with large surface areas, which are often designed for energy and environment applications, have also demonstrated enhanced water evaporation rates due to the improved transpiration pathways compared to 2D structures . Some 3D solar steamers also exploit environmental energy and reach 100% efficiency in solar‐to‐vapor energy transfer .…”
mentioning
confidence: 99%
“…In addition to the above study and analysis, the outstanding evaporation rates and energy conversion efficiency of the origami rose can also be understood from the perspective of operating temperatures of a solar steamer (Figure c,d). It has been observed that operating temperatures of 3D solar steamers are lower than those of their 2D counterparts . This can be attributed to the enlarged specific surface areas that allow more solar induced thermal energy to vaporize water, resulting in lower surface temperature.…”
mentioning
confidence: 99%
“…The solar evaporation rate is calculated to be 2.28 kg m −2 h −1 (Figure S9, Supporting Information). The performance of the 3D CMF was compared to the recently reported evaporators (Figure c) . Obviously, the 3D CMF shows excellent evaporation rates both in dark and under illumination.…”
Section: Resultsmentioning
confidence: 96%
“…The performance of the 3D CMF was compared to the recently reported evaporators (Figure 4c). [30][31][32][33][34][35] Global Challenges 2019, 3,1900040 Obviously, the 3D CMF shows excellent evaporation rates both in dark and under illumination. What's more, the evaporation rate shows no dependence on water quantity ( Figure S15, Supporting Information) and responses fast to the irradiation change ( Figure S16, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%